A Rare Case of Recurrent Renal Infarcts With Unique Etiologies in Different Kidneys Occurring Six Years Apart - Kaitlyn Perkins; Emilyn Anderi; Mariam Costandi; Karla D. Passalacqua; Katarzyna Budzynska (Case Reports in Nephrology)
Renal infarcts are uncommon, difficult to diagnose, and can lead to long-term kidney disease. Because they have numerous etiologies and patients may present with nonspecific symptoms, renal infarcts may be mistaken for other common conditions. A 50-year-old woman presented to the emergency department (ED) with flank pain, nausea, and vomiting. Computed tomography (CT) revealed multiple right kidney infarcts, transthoracic echocardiography revealed mitral valve stenosis with no evidence of atrial fibrillation, and hypercoagulability tests were negative. High-intensity anticoagulation therapy resolved the infarcts and she was discharged on warfarin. Six years later, at the age of 56, the woman again presented to the ED with back pain, nausea, vomiting, and fever. She had undergone valvuloplasty to repair the mitral valve stenosis 1 month before this ED visit, and warfarin had been discontinued shortly after the procedure. CT imaging and ultrasonography showed no evidence of infarcts and electrocardiogram was normal. Although urinalysis was negative for infection, pyelonephritis was suspected per CT results. However, renal function and leukocytosis did not improve after 2 days of antibiotic therapy. Radioisotope renal scan then revealed infarcts in the left kidney. Anticoagulation therapy again led to recovery, and the patient was discharged back on warfarin. After the recurrent infarct, monitoring and cardiac care have led to adequate long-term management, and no evidence of atrial fibrillation has ever been observed. This case illustrates the challenging diagnosis of an unusual presentation of recurrent renal infarct, where each infarct was suspected to have a unique and independent etiology: mitral valve stenosis in the first and hypercoagulability from withdrawal of warfarin in the second. Because no clear risk or symptom profiles exist for renal infarcts, this unusual condition should be considered when patients do not respond to treatment for other renal problems, especially those with cardiovascular disease.